PENGARUH PENGAWASAN KEPALA SEKOLAH TERHADAP EFEKTIVITAS PELAKSANAAN PROGRAM INDONESIA PINTAR (PIP) DI SMPN 1 WARUNGKIARA KABUPATEN SUKABUMI - Hilyatul Auliya (Mimbar Administrasi Mandiri, 2023)
The research departs from a problem namely the effectiveness of the smart Indonesia Program is not yet optimal, one of the factors considered to influence the not yet optimal implementation of the Smart Indonesia Program. Researchers use the theory of Supervision according to Siagian (2017 :114-115) and the theory of effectiveness according to Saxena in Indrawijaya (2010:176).Researchers used a quantitative approach, the samples used were 108 people from a population of 893 people taken by probability sampling technique with the Disproportionate stratified random sampling method and the Slovin formula tool. There are two variables studied in this study, namely Head Master Supervision (VX) and the Effectiveness of the Implementation of the Smart Indonesia Program (VY). The main instrument used in this research is a questionnaire with a rating scale of 5 (five) choices. The data collected was then analyzed using descriptive analysis techniques using item averages, while statistical analysis techniques using correlation analysis, and simple linear regression equation models. The calculation results show that the cumulative average yield of the Head master Supervision variable is 4.04 which is included in the good category, while the Effectiveness of the Implementation of the Smart Indonesia Program is 4.08 which is included in the good category. The results of the statistical analysis obtained the price of r_xy = 0.708 which is included in the strong category with a significance value of (2-tailed) 0.000 > 0.005 or t_count = 10.33 > t_table = 1.982 so it can be concluded that Leadership Oversight has a positive and significant effect on the Effectiveness of the Implementation of the Smart Indonesia Program while the Coefficient of Determination (KD) is 0.501 which means that 50,1% of the Effectiveness of the Implementation of the Smart Indonesia Program (Y) can be explained by the Head master Supervision variable (X) and the rest is determined by other factors. Furthermore, the linear regression equation model is Ŷ = 16,045 + 0.747X. Therefore, to increase the results of the Implementation of the Smart Indonesia Program, it is suggested to the Head master to improve the Supervision function.